2016
DOI: 10.1016/j.cjca.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With Atrial Fibrillation in Administrative Data

Abstract: Identifying patients with AF can be done using administrative data, and the algorithm can be used to assess trends in disease burden over time and patterns of care in large populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 4 publications
5
76
0
Order By: Relevance
“…The cohort consisted of all adult Albertans (aged 18 years or older) with a diagnosis of AF or atrial flutter (International Classification of Diseases-9 CM 427.3 and ICD-10 CA I48) between January 1, 2008 and March 31, 2014 in any fields of either the discharge abstract database (DAD; which captures all acute care hospitalizations with most responsible diagnosis and up to 24 secondary diagnoses), the national ambulatory care reporting system (NACRS; which captures all visits to emergency rooms or hospital-based specialist clinics in Alberta), or the physician billing claims databases (see eTable 1 for case definitions for AF and valvular AF). These AF case definitions have been evaluated in multiple studies and in those that used both inpatient and outpatient data (as we did) sensitivity approached 95% and specificity 99% [15][16][17][18][19]. Of note, we defined any patients with mitral stenosis or a valve procedure as having "valvular AF" and all others as having "NVAF" [20].…”
Section: Study Samplementioning
confidence: 98%
See 1 more Smart Citation
“…The cohort consisted of all adult Albertans (aged 18 years or older) with a diagnosis of AF or atrial flutter (International Classification of Diseases-9 CM 427.3 and ICD-10 CA I48) between January 1, 2008 and March 31, 2014 in any fields of either the discharge abstract database (DAD; which captures all acute care hospitalizations with most responsible diagnosis and up to 24 secondary diagnoses), the national ambulatory care reporting system (NACRS; which captures all visits to emergency rooms or hospital-based specialist clinics in Alberta), or the physician billing claims databases (see eTable 1 for case definitions for AF and valvular AF). These AF case definitions have been evaluated in multiple studies and in those that used both inpatient and outpatient data (as we did) sensitivity approached 95% and specificity 99% [15][16][17][18][19]. Of note, we defined any patients with mitral stenosis or a valve procedure as having "valvular AF" and all others as having "NVAF" [20].…”
Section: Study Samplementioning
confidence: 98%
“…Of note, we defined any patients with mitral stenosis or a valve procedure as having "valvular AF" and all others as having "NVAF" [20]. We included all patients with AF but defined newly diagnosed (incident) cases as those without any of the relevant AF diagnostic codes prior to January 2008 (and as far back as April 1994)patients could only remain in the "newly diagnosed" subtype for the first year after diagnosis but they continued in the cohort after that year and contributed to the numerators/denominators for prevalent cases after that time [19,21]. For all AF case definitions, the index date was defined as the date of the first AF code in the DAD, NACRS, or physician billing claims databases.…”
Section: Study Samplementioning
confidence: 99%
“…Our study ended in 2014, and most prescriptions were for warfarin; however, warfarin use is decreasing as direct oral anticoagulant use is increasing. 57,58 This shift may make it more likely that emergency and family physicians will initiate oral anticoagulation, but the impact of starting oral anticoagulation in the emergency department is unlikely to change substantially. We included all patients who qualified for stroke prevention on the basis of CHADS-65, but in the earlier years of this study, CHADS 2 combined with CHA 2 DS 2 -VASc was recommended; 55 therefore, some of the early patients would not have qualified for oral anticoagulants.…”
Section: Limitationsmentioning
confidence: 99%
“…New onset of atrial fibrillation following cardiac surgery, referred to as postoperative atrial fibrillation (POAF), is a common complication, occurring in approximately 20 to 60% of patients depending on the type of surgical interventions performed [1]. Prior studies have shown that POAF is associated with important morbidity, mortality, and costs [1][2][3][4][5]. Specifically, POAF markedly increases the risk of embolic events (e.g., stroke, thromboembolism), cardiac complications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, POAF markedly increases the risk of embolic events (e.g., stroke, thromboembolism), cardiac complications (e.g. heart failure, myocardial infarction, cardiac arrest), as well as renal and respiratory failure [1,2,5]. Moreover, POAF doubles the risk of both 30-day and 6-month mortality [1].…”
Section: Introductionmentioning
confidence: 99%